If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -5p = q Solving 7 + -5p = q Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -5p = -7 + q Combine like terms: 7 + -7 = 0 0 + -5p = -7 + q -5p = -7 + q Divide each side by '-5'. p = 1.4 + -0.2q Simplifying p = 1.4 + -0.2q
| 8i-(-14-9i)= | | Y-1.6=7 | | 2x+6.4=x | | 4m+(3m-1)=19 | | 3-12+6=13+x-5 | | -6x+5=-67 | | 8x+8y+8z= | | x^2+4x-390=0 | | 3R(4-k)=2-R | | X+3.5=5.5-x | | 15x-9=3(5x+8) | | 4c-5=37 | | 7=4.7n-8.25-7.2n | | n*2.25=90 | | 8y+9= | | 4/9w-14=-5/6w | | -2(4x+3)=4(1-2x)-10 | | 7x+9.06=5x+12 | | 43650=45000+75m | | (4X-4)+(3x+2)=180 | | -2v-8= | | 64+5x=7x+64 | | 6x=6x+9 | | C=15d+250 | | 11x=180-16 | | 11-(2v+3)= | | X-5=4.81 | | 5-3x-7+6x= | | Ft-3+4t=(3t-9) | | 10(4)-12=5(4)+8 | | 5h+6k-5(3h-9k)= | | 3x-8=-2x-8 |